2024
DOI: 10.1007/s40820-024-01353-0
|View full text |Cite
|
Sign up to set email alerts
|

ROS Balance Autoregulating Core–Shell CeO2@ZIF-8/Au Nanoplatform for Wound Repair

Xi Zhou,
Quan Zhou,
Zhaozhi He
et al.

Abstract: Reactive oxygen species (ROS) plays important roles in living organisms. While ROS is a double-edged sword, which can eliminate drug-resistant bacteria, but excessive levels can cause oxidative damage to cells. A core–shell nanozyme, CeO2@ZIF-8/Au, has been crafted, spontaneously activating both ROS generating and scavenging functions, achieving the multi-faceted functions of eliminating bacteria, reducing inflammation, and promoting wound healing. The Au Nanoparticles (NPs) on the shell exhibit high-efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Platinum acts as a catalyst to break down H 2 O 2 to produce oxygen for wound healing [118]. Deng et al have hydrogel-based wound dressing via encapsulation of Au@MOF nanoparticles for [116] improved antibacterial activities to heal wounds healing under visible light sources. They have reported that the composite hydrogel biomimic is the natural extracellular matrix and has performed not only antibacterial activities against Gram-positive and Gramnegative bacterial strains but also enhanced wound healing [112].…”
Section: Light-drivingmentioning
confidence: 99%
“…Platinum acts as a catalyst to break down H 2 O 2 to produce oxygen for wound healing [118]. Deng et al have hydrogel-based wound dressing via encapsulation of Au@MOF nanoparticles for [116] improved antibacterial activities to heal wounds healing under visible light sources. They have reported that the composite hydrogel biomimic is the natural extracellular matrix and has performed not only antibacterial activities against Gram-positive and Gramnegative bacterial strains but also enhanced wound healing [112].…”
Section: Light-drivingmentioning
confidence: 99%